The metabolic addiction of cancer stem cells - Sahoo, Om Saswat; Pethusamy, Karthikeyan; Srivastava, Tryambak P.; Talukdar, Joyeeta; Alqahtani, Mohammed S.; Abbas, Mohamed; Dhar, Ruby; Karmakar, Subhradip (Frontiers in Oncology, 2022)
Cancer stem cells (CSC) are the minor population of cancer originating cells that have the capacity of self-renewal, differentiation, and tumorigenicity (when transplanted into an immunocompromised animal). These low-copy number cell populations are believed to be resistant to conventional chemo and radiotherapy. It was reported that metabolic adaptation of these elusive cell populations is to a large extent responsible for their survival and distant metastasis. Warburg effect is a hallmark of most cancer in which the cancer cells prefer to metabolize glucose anaerobically, even under normoxic conditions. Warburg’s aerobic glycolysis produces ATP efficiently promoting cell proliferation by reprogramming metabolism to increase glucose uptake and stimulating lactate production. This metabolic adaptation also seems to contribute to chemoresistance and immune evasion, a prerequisite for cancer cell survival and proliferation. Though we know a lot about metabolic fine-tuning in cancer, what is still in shadow is the identity of upstream regulators that orchestrates this process. Epigenetic modification of key metabolic enzymes seems to play a decisive role in this. By altering the metabolic flux, cancer cells polarize the biochemical reactions to selectively generate “onco-metabolites” that provide an added advantage for cell proliferation and survival. In this review, we explored the metabolic-epigenetic circuity in relation to cancer growth and proliferation and establish the fact how cancer cells may be addicted to specific metabolic pathways to meet their needs. Interestingly, even the immune system is re-calibrated to adapt to this altered scenario. Knowing the details is crucial for selective targeting of cancer stem cells by choking the rate-limiting stems and crucial branch points, preventing the formation of onco-metabolites.